Anesthesia for Off Pump Coronary Artery Bypass Surgery in a Patient with Brain Tumor - Rawat, Sarwan K S; Shrestha, Battu Kumar; Juneja, Rajiv; Mehta, Yatin; Trehan, Naresh (Nepalese Heart Journal, 2019)
The outcome after off pump coronary artery bypass grafting (OPCAB) surgery has been promising. These good outcomes relate to the benefits of avoiding extra corporeal circulation. Some of the reported advantages include a lower incidence of renal complications, pulmonary complication, adverse neurological event, reduced transfusions requirement and attenuation of the systemic inflammatory response. If the patient has associated preoperative complicated neurological issues, then perioperative management will be more challenging and requires extensive care and precautions.We present a case with symptomatic meningioma and unstable angina who underwent successful urgent OPCAB surgery without further neurological deterioration.